Medical and Dental Implications of Down Syndrome: A Review Part 1: General and Craniofacial Characteristic - Ghaith, Batool; B. Kowash, Mawlood; El-Halabi, Manal (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2016)
Down syndrome (DS) is a genetic disorder characterized by the presence of three chromosomes instead of two, specifically chromosome No. 21. The special needs status of DS individuals makes them more prone to several medical conditions such as congenital heart disease, gastrointestinal tract anomalies, immunodeficiency, visual impairment, skeletal defects, audiological dysfunction, seizures, acute leukaemia and thyroid disorders. A thorough knowledge of the unusual medical and orofacial abnormalities and their implications is crucial for a successful dental preventive and treatment planning. This paper provides an updated review of DS definition, etiology, epidemiology, medical problems and dentofacial abnormalities.
Keywords: atlanto-axial joint instability